2013
DOI: 10.1002/ejhf.16
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prognostic impact of therapeutic strategies in patients with idiopathic dilated cardiomyopathy: changing mortality over the last 30 years

Abstract: Aims ACE‐inhibitors, β‐blockers, implantable cardioverter–defibrillator (ICD) and cardiac resynchronization therapy (CRT) improved prognosis of heart failure. We sought to analyse the long‐term prognostic impact of evidence‐based integrated therapeutic strategies in patients with idiopathic dilated cardiomyopathy (IDCM). Methods and results From 1978 to 2007, 853 IDCM patients (45 ± 15 years, 72% males) were enrolled and classified as follows: Group 1, 110 patients (12.8%) enrolled during 1978–1987; Group 2, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
149
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 35 publications
3
149
0
7
Order By: Relevance
“…Exclusion criteria included arterial hypertension (>140/90 mm Hg),12 coronary artery disease (obstruction >50% of the luminal diameter in a major branch by coronary angiography), history of chronic excess alcohol consumption (>100 g/d), tachycardia‐induced cardiomyopathy, systemic diseases affecting short‐term prognosis, pericardial disease, congenital heart disease, and cor pulmonale 8, 13…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included arterial hypertension (>140/90 mm Hg),12 coronary artery disease (obstruction >50% of the luminal diameter in a major branch by coronary angiography), history of chronic excess alcohol consumption (>100 g/d), tachycardia‐induced cardiomyopathy, systemic diseases affecting short‐term prognosis, pericardial disease, congenital heart disease, and cor pulmonale 8, 13…”
Section: Methodsmentioning
confidence: 99%
“…1,2 The prevalence of DCM in the general population is thought to be &40 to 50 cases per 100,000 and the incidence is 6.95/100,000 new cases a year, but this is a rough estimation since there is a growing evidence that the course of the illness is asymptomatic and difficult to recognize for a long period. 3,4 Transplant-free survival has improved in the last three decades from 55% to 71% and 87% at 8 years 5 thanks to early diagnosis, effective management, and evidence-based integrated therapeutic approach including multiple drug therapy, implantable defibrillators, and cardiac resynchronization (CRT) treatments. Despite this success, DCM remains in most patients, a progressive disease with large individual variability and a poor prognosis.…”
Section: See Related Article Pp 758-767mentioning
confidence: 99%
“…In a large cohort of an Italian DCM population from the Heart Muscle Diseases Registry of Trieste, it has been shown that nowadays the incidence of major adverse cardiac events in patients affected by DCM is less than 2% per year, the survival free of transplantation at 8 years from diagnosis is more than 85% and the incidence of SCD is less than 0.5% per year. [2] Pharmacological treatment is the cornerstone for preventing the progression of the disease. According to the most recent guidelines, ACE-I, β-blockers and mineralocorticoid antagonists are the pillar therapeutic agents demonstrated to improve survival in patients affected by HF.…”
Section: Left Ventricular Reverse Remodeling: the Concept Of Dynamic mentioning
confidence: 99%
“…[1] Once symptoms develop, DCM usually leads to decompensated heart failure (HF) and it represents one of the most common causes of heart transplantation (HTx) in the Western world. [2] On the other hand often life-threatening arrhythmias and sudden cardiac death (SCD) can importantly characterize the course of DCM or represent the abrupt onset of the disease. [3] Management of DCM is currently particularly difficult for the clinicians.…”
mentioning
confidence: 99%